Analisis Keberhasilan Usaha Rumah Makan Salero Basamo Dalam Mempertahankan Keeksistensian Ditengah Persaingan Rumah Makan Yang Sejenis di Kota Gunungsitoli - Mei Kristian Halawa; Emanuel Zebua; Yupiter Mendrofa; Otanius Laia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
This research was conducted at the Salero Basamo Restaurant, Gunungsitoli City. This research aims to successfully determine the Salero Basamo restaurant business in maintaining its existence amidst competition from similar food stall businesses. This research uses a qualitative descriptive method, using data sources, namely observation, interviews, documentation. In the research, determining informants used purposive sampling and snowball sampling techniques to obtain 3 key informants who could provide information related to problems at the research site. The results of this research show that the success of a business in maintaining its existence can be seen from the level of customer satisfaction and competitive advantage.